Analisis Strategi Inovasi Produk Dan Pemasaran Digital Dalam Upaya Peningkatan Daya Saing Produk UMKM (Studi Kasus Toko Roti Dewi) - Abdul Tahar; Ega Saiful Subhan; Fahrudin Fahrudin (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the product innovation and digital marketing strategies implemented by Toko Roti Dewi in Dompu Regency to enhance the competitiveness of SMEs. The research employed a descriptive qualitative method with data collected through semi-structured interviews, observation, and documentation. The findings reveal that product innovation strategies include seasonal product development, modification of taste and packaging, utilization of local raw materials, addition of new menu variants, and the use of modern production technology. Digital marketing strategies consist of social media utilization, online marketplaces, online promotions, interactive communication with customers, and the creation of simple visual content. The results indicate that WhatsApp is the dominant marketing channel because it provides fast, personal, and flexible communication compared to marketplaces. The consistent implementation of product innovation combined with digital marketing strategies has been proven to increase customer loyalty, expand market reach, and strengthen SME competitiveness amid growing business competition.